1998
DOI: 10.1044/jslhr.4102.374
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Skills of Children With Specific Expressive Language Impairment (SLI-E)

Abstract: Naturalistic speech samples of 29 3-year-olds diagnosed with specific expressive language delay (SU-E) were compared to those produced by 19 age-matched normally developing peers in order to determine their improvement in phonological skills since age 2, when Rescorla and Ratner (1996) studied them. Specifically, the groups were compared with regard to vocalization rate, verbalizations, fully intelligible utterances, phonetic inventories, percentages of consonants correct (PCC), phonological processes, and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
1
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 21 publications
7
36
1
3
Order By: Relevance
“…In particular, the study focussed on identifying early differences in syllable structure and phonetic characteristics of babbling and first words between the two groups, in order to identify reliable indicators of language development. Our data, collected on a sample of Italian children, are consistent with those reported by previous studies (McCathren, Yoder and Warren, 1999;Mirak and Rescorla, 1998;Paul and Jennings, 1992;Pharr, Ratner and Rescorla, 2000;Rescorla and Ratner, 1996;Roberts, Rescorla, Giroux and Stevens, 1998;Stoel-Gammon, 1989;Thal, Oroz and McCaw, 1995): children 14 who show a low expressive language development at 24 months exhibited significantly different babbling patterns and syllable structures than those of their TD peers at 18-20 months of age. Many authors posited the predictive value of babbling characteristics with regard to subsequent speech and language ability (Davis and MacNeilage, 1995;StoelGammon, 1989;Vihman, 1996), in so far the experience of frequent self-producing CV syllables made infants more aware of similar patterns in their ambient language, rendering these forms more salient as potential building blocks for word representations.…”
Section: Discussionsupporting
confidence: 89%
“…In particular, the study focussed on identifying early differences in syllable structure and phonetic characteristics of babbling and first words between the two groups, in order to identify reliable indicators of language development. Our data, collected on a sample of Italian children, are consistent with those reported by previous studies (McCathren, Yoder and Warren, 1999;Mirak and Rescorla, 1998;Paul and Jennings, 1992;Pharr, Ratner and Rescorla, 2000;Rescorla and Ratner, 1996;Roberts, Rescorla, Giroux and Stevens, 1998;Stoel-Gammon, 1989;Thal, Oroz and McCaw, 1995): children 14 who show a low expressive language development at 24 months exhibited significantly different babbling patterns and syllable structures than those of their TD peers at 18-20 months of age. Many authors posited the predictive value of babbling characteristics with regard to subsequent speech and language ability (Davis and MacNeilage, 1995;StoelGammon, 1989;Vihman, 1996), in so far the experience of frequent self-producing CV syllables made infants more aware of similar patterns in their ambient language, rendering these forms more salient as potential building blocks for word representations.…”
Section: Discussionsupporting
confidence: 89%
“…For example Fee [12] found that the most common simplifi cation processes were cluster reduction, omission of onset syllables, substitution of liquid sounds in the initial syllable and devoicing of fi nal segments, which is consistent with our own fi ndings; this researcher also found the same order of acquisition in SLI subjects and non-impaired ones. In line with Rescorla and Bernstein-Ratner [8] and Rescorla et al [9] we found that children with SLI continue to show a delay in phonology as they grow, and, consistent with these studies, we found great variability in the SLI group. Our results are also in agreement with those of Owen et al [25] and Nettelbladt [26] in that we found the most usual processes to be syllabic reductions and substitutions.…”
Section: Discussionsupporting
confidence: 79%
“…We could determine the set of consonants that children articulate, and we could describe their misarticulations. For example, many of the speech production errors of normal preschoolers (e.g., articulatory distortions) resolve spontaneously by school age or earlier in a predictable manner (Roberts et al, 1998;Shriberg et al, 1986). Most preschool children correctly produce /m/ but many do not produce adult-like /s/ sounds.…”
Section: Introductionmentioning
confidence: 97%